HUBUNGAN MUSIK DENGAN TARI PIRIANG RANTAK TAPI DIKANAGARIAN PITALAH - Nurnela Hardi; Yensharti Yensharti; Syeilendra Syeilendra (FBS Universitas Negeri Padang, 2014)
Abstract The aim of this study was to figure out the correlation between the music with the dance in Tari Piriang Rantak Tapi show. This was a qualitative research which used content analysis approach. The data was collected through library study, observation and interview. The data then was classified into primary and secondary data. The result of the research revealed that there was a very significant correlation between the music and the dance in Tari Piriang Rantak Tapi show. Each of them affected to each other so that they became a unity. The music accompanied the dance in accordance with the structur of the dance. It also created a harmonic atmosphere which support the dance show. In counting the beats or rhythmic of the music and dance, it was clearly that the beats were one times eight which was similar to the strains of the music using 4/4 of birama symbol. As a whole, it has 11 kinds of movements. Keyword : Tari Piriang Rantak Tapi, Relation, Music, and Dance